Improving Teaching Performance Development: The Implementation of Results-Based Performance Management System (RPMS) - Jaynard Esteban; Rosanie Estuche; Romulo Navarra; Marie Jo Tess Ragos; Roberto Tampil; Cynic J. Tenedero (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This is quantitative descriptive research that analyzes the Results-Based Performance Management System (RPMS) used as performance management tool for the teachers. The Results-Based Performance Management System was gathered through survey questionnaire. The assessment focused on the extent of implementation in terms of Performance Planning and Commitment; Performance Monitoring and Coaching; Performance Review and Evaluation; and Performance Rewards and Development Planning. There are 161 teacher respondents from the four (4) public elementary schools of District III in the Division of Makati City. The extent of implementation of the Results-Based Performance Management System in terms of Performance Planning and Commitment and Performance Monitoring and Coaching were interpreted to a great extent with a weighted mean of 4.13 and 4.05 respectively. Meanwhile, in terms of Performance Rewarding and Planning and Performance Review and Evaluation, the respondents assessed as a great extent with the same weighted mean of 4.09. It was evident that the implementation of Results-Based Performance Management System (RPMS) improves teachers personally and professionally, there is a need that this program must be enhanced. Moreover, implementing such program helps teachers improve their practice in the teaching-learning process which will drive them to achieve better performance. There should be proper review to develop a program plan that addresses the challenges of the performance.